Alloplasty for bone defects resulting from the removal of benign tumours and tumour-like lesions - Marin, Ivan; Kaprosh, Nikolay; Mihul, Nikolay; Vukolova, Vera; Baciu, Ivan; Orlov, Viktor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article describes experience of treatment of 537 patients, in whom their defects that formed after removal of benign tumours and tumour-like lesions were replaced with bone allografts. Results of the treatment were assessed as positive in 95.1 % of cases and unsatisfactory in 4.9 %. Clinical, radiological and morphological studies showed that in children their split cortical bone allografts completely reformed with normalization of the bone structure and formation of the intramedullary canal during 2-3 years after the operation. In adults, this process lasted up to 25 years and longer; its course was favourable. Allogenic epiphyses (22 patients) reformed in the area of their contact with the bone and soft tissues of the recipient very slowly. The rest of the graft was preserved as a biological endoprosthesis. Formalinized allobone as plastic material was clearly superior and gave a big economic effect.